2005
DOI: 10.1111/j.1540-8191.2005.200318.x
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of Local Wound Anesthesia to Reduce Postoperative Pain After Median Sternotomy

Abstract: Postoperative pain control still represents a major challenge in every surgical field. Bupivacaine wound infiltration is frequently used to reduce the pain related to the surgical incision itself. In this randomized study, we investigated the efficacy of bupivacaine local anesthesia after median sternotomy to reduce postoperative pain. Forty-seven patients undergoing major cardiac surgery procedures were allocated randomly to group A (bupivacaine wound infiltration 0.5%; 10 mL, followed by continuous infusion:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Analgesia was significantly improved but a weakness of this study was that the small number of patients underwent a variety of unmatched surgical procedures. In contrast, Mangano did not improve analgesia after sternotomy [27]. However, in this study, only 10 ml bupivacaine 0.5% was used to infiltrate the entire wound subcutaneously at the end of surgery , followed by a low volume infusion of 5 ml.h −1 , ensuring poor LA distribution throughout the wound.…”
Section: Surgical Applicationsmentioning
confidence: 86%
“…Analgesia was significantly improved but a weakness of this study was that the small number of patients underwent a variety of unmatched surgical procedures. In contrast, Mangano did not improve analgesia after sternotomy [27]. However, in this study, only 10 ml bupivacaine 0.5% was used to infiltrate the entire wound subcutaneously at the end of surgery , followed by a low volume infusion of 5 ml.h −1 , ensuring poor LA distribution throughout the wound.…”
Section: Surgical Applicationsmentioning
confidence: 86%
“…Muller et al [46] showed that 51% of heart surgery patients still had sternotomy pain on the 7 th postoperative day. In the postoperative period, routine procedures such as movement in bed and mediastinal drain manipulation can influence respiration mechanics and cough ability [47,48]. Another factor that contributes to impaired lung function and respiratory mechanics is the cardiopulmonary bypass (CPB) itself.…”
Section: Discussionmentioning
confidence: 99%
“…[126][127][128][129][130][131][132][133] No evidence regarding their effect on the development of chronic pain exists. 126 …”
Section: Continuous Wound Cathetermentioning
confidence: 99%